2013
DOI: 10.1016/j.freeradbiomed.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial NO and O2− production rates differentially regulate oxidative, nitroxidative, and nitrosative stress in the microcirculation

Abstract: Endothelial dysfunction causes an imbalance in endothelial NO and O2•− production rates and increased peroxynitrite formation. Peroxynitrite and its decomposition products cause multiple deleterious effects including tyrosine nitration of proteins, superoxide dismutase (SOD) inactivation and tissue damage. Studies have shown that peroxynitrite formation during endothelial dysfunction is strongly dependent on the NO and O2•− production rates. Previous experimental and modeling studies examining the role of NO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 93 publications
0
18
0
Order By: Relevance
“…An imbalance between nitric oxide and nitric oxide contributes to the pathophysiological process of cardiovascular diseases. Reduction in nitric oxide release contributes to ROS generation, whereas nitric oxide release decreases the level of ROS [54]. Moreover, nitric oxide release is triggered by imidazoline-like drugs such as clonidine and moxonidine [55], suggesting a possibility that nitric oxide mechanism contributes to moxonidine-mediated antioxidant action in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance between nitric oxide and nitric oxide contributes to the pathophysiological process of cardiovascular diseases. Reduction in nitric oxide release contributes to ROS generation, whereas nitric oxide release decreases the level of ROS [54]. Moreover, nitric oxide release is triggered by imidazoline-like drugs such as clonidine and moxonidine [55], suggesting a possibility that nitric oxide mechanism contributes to moxonidine-mediated antioxidant action in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies showed that NO also reacts with oxygen and superoxide anion to form nitrogen dioxide and peroxynitrite anion, which are known cytotoxic oxygen radicals 49. İncreased peroxynitrite concentration causes endothelial dysfunction 50. In another study examining NO in AMD, the NO levels were found to be lower in AMD patients than in controls, but the underlying mechanism was not described.…”
Section: Discussionmentioning
confidence: 99%
“…Using a systems biology approach, we showed that hyperglycemia induces the production of H 2 O 2 in human umbilical vein endothelial cells (HUVEC) (Patel et al, 2013). Additionally, the presence of high ROS levels are shown to promote a pro-oxidative redox response in endothelial cells (Coyle et al, 2006; Kar and Kavdia, 2013). Thus, the interplay between a high H 2 O 2 level and a dysfunctional endothelium can lead to a system wide progression of endothelial dysfunction in a feed-forward manner (Kar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%